2019
DOI: 10.1093/geront/gnz074
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Biographical Approaches in Long-Term Care: A Systematic Review

Abstract: Background and Objectives Older adults in long-term residential aged care experience loneliness and reduced quality of life (QoL). Biographical approaches use the recall of the past events to increase self-efficacy, promote acceptance, and improve QoL. The aim of the systematic review was to examine the effectiveness of biographical approaches in improving the QoL of older adults in long-term residential aged care. Research Design and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…QOL means a sense of satisfaction with life and overall or subjective wellbeing, as influenced by health status, relationship with others, self-concept, and environment [7][8][9]. In fact, QOL is reportedly an indicator of quality of care [8,10,11]. Several QOL indicators have been developed and used in medical research as health-related QOL [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…QOL means a sense of satisfaction with life and overall or subjective wellbeing, as influenced by health status, relationship with others, self-concept, and environment [7][8][9]. In fact, QOL is reportedly an indicator of quality of care [8,10,11]. Several QOL indicators have been developed and used in medical research as health-related QOL [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable approaches such as 'simple reminiscence', 'life-review', or 'life-review therapy' [21,22] have been used successfully in patients with dementia and older persons [21,[23][24][25]. While 'simple reminiscence' focuses on the recall and sharing of memories, 'life review' is more evaluative and aims to cover the whole life story chronologically.…”
Section: Introductionmentioning
confidence: 99%
“…Storytelling may enable older adults to feel recognized, affirmed, empowered, and accomplished and may assist in building resilience [ 8 - 10 ]. Reviews of studies have suggested that activities that include reminiscence about one’s life story may improve subjective psychological well-being, quality of life, mood, and cognition [ 11 - 14 ]. In addition, reviews have found that activities that involve reminiscence have the potential to improve quality of life, cognition, communication, and activities of daily living in older adults living with Alzheimer disease and dementia [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%